Controlling of optical band gap of the CdO films by zinc oxide - Kati, Nida (De Gruyter Poland Sp Zoo, 2019)
In this study, CdZnO films prepared at different ratios of dopants (CdO: ZnO = 5: 5, CdO: ZnO = 6: 4, and CdO: ZnO = 8: 2) were coated on glass surface by using the sol-gel spin coating technique. After this process, surface structure and optical properties of the CdZnO films was investigated by atomic force microscopy (AFM) and UV-Vis spectroscopy. The surface structure of the CdZnO films depended on the content of ZnO and CdO in the films. Low percentage of CdO films were very similar to the ZnO film but higher amount of CdO resuted in granular structures together with pure structure of ZnO in the films. Eg values of produced CdZnOs depended on the additions of CdO and ZnO. The obtained Eg values of the produced CdO: ZnO = 5: 5 (S3), CdO: ZnO = 6: 4 (S4), and CdO: ZnO = 8: 2 (S5) films are 2.5 eV, 2.49 eV, and 2.4 eV, respectively.
Keywords: thin film; spin coating; ZnO; CdO; optical properties